User Satisfaction Role in Mediating Enterprise Resource Planning (ERP) System Effectiveness (Journal of Informatics and Mathematical Sciences, 2017)
Over the past, a decade, companies in Malaysia show deep interest in implementing the Enterprise Resource Planning (ERP) system to improve their business processes. Due to the capability offered by this so-called robust system, it yields interest in companies to implement this system but is lacking in knowledge on the impact after the execution of the system. Notionally, the effectiveness of the system can be measured only after successfully implementing the system. The user acceptance and satisfaction of using the system thus need to be investigated to measure its effectiveness. This research is conducted via a cross-sectional survey of 150 respondents. The responses were analyzed with employing structural equation modeling (SEM). The role of user satisfaction as a mediator is addressed in identifying the most important and significant factors contributing to the effectiveness of ERP system. Findings of this study revealed that the highest contribution was due to service quality where user satisfaction factor is embedded as a mediator in the SEM model of studying the relationship of service quality towards net benefits.
Keywords: Enterprise Resource Planning (ERP); Service Quality; User Satisfaction; Telecommunication; IS Effectiveness